(Au, Ag)Te2 Minerals from Epithermal Gold Deposits in Japan. Issue 1 (January 2017) - Komuro, Kosei; Nakata, Masataka
Abstract: Chemical composition and mode of occurrences of (Au, Ag)Te2 minerals such as calaverite (AuTe2 ), sylvanite (AuAgTe4 ) and krennerite ((Au, Ag)Te2 ) in epithermal gold telluride ores from Suzaki, Kawazu and Teine are examined. In the ores from Suzaki, (Au, Ag)Te2 minerals occur in microbands of tellurides and fine quartz. The minerals in telluride bands change from krennerite, via calaverite‐native tellurium, to sylvanite, in the order of crystallization. A sample from Kawazu contains sylvanite and native tellurium with stutzite, hessite and tetradymite in the coarser gray quartz part. The Teine sample also contains sylvanite and native tellurium with barite and quartz. The peak patterns of XRD of calaverite, krennerite and sylvanite from Suzaki are almost identical to that of JCPDS 43–1472, JCPDS 8–20 and JCPDS 9–477, respectively. The Te, Au, Cu, and Ag contents of calaverite from Suzaki range from 56.4 to 57.9 wt.%, from 41.6 to 42.6 wt.%, from 0.28 to 0.45 wt.% and from 0.14 to 0.31 wt.%, respectively, corresponding to the formula Au0.97 Ag0.01 Cu0.02 Te2 . The Te, Au, Ag, and Cu contents of krennerite from Suzaki range from 59.6 to 61.4 wt.%, from 31.3 to 33.6 wt.%, from 4.91 to 6.13 wt.% and from 0.66 to 0.80 wt.%, respectively, corresponding to the formula Au0.71 Ag0.22 Cu0.05 Te2 with Au and Ag ranging from 0.68 to 0.74 and from 0.20 to 0.25, respectively. The Te, Au, Ag, and Cu contents of sylvanite from Suzaki range from 61.5 to 63.4 wt.%, from 24.1 to 27.4 wt.%, from 10.0 to 12.5 wt.% and from 0.00 to 0.12 wt.%, respectively. The Te, Au, Ag, and Cu contents of sylvanite from Kawazu range from 62.7 to 63.3 wt.%, from 23.5 to 24.1 wt.%, from 12.0 to 12.5 wt.% and from 0.09 to 0.16 wt.%, respectively. The Te, Au, Ag, Cu and Fe contents of sylvanite from Teine range from 61.8 to 63.5 wt.%, from 23.6 to 24.7 wt.%, from 11.9 to 13.3 wt.%, from 0.01 to 1.65 wt.% and from 0.00 to 0.02 wt.%, respectively. The average formulae of sylvanite from Suzaki, Kawazu, and Teine are expressed as Au1.06 Ag0.94 Cu0.02 Te4, Au1.00 Ag0.95 Cu0.02 Te4 and Au1.01 Ag0.95 Cu0.06 Te4, respectively. Judging from the mineral assemblages of these ores and other localities, Au–Te mineralization in the Japanese Islands can be divided into four types: native gold–calaverite at Date and Agawa, krennerite(−native tellurium) at Osore‐zan and Mutsu, sylvanite–native tellurium–hessite at Teine, Kawazu, Kobetsuzawa, and Kato, and polyminerallic assemblages at Suzaki and Kushikino. The pH–Eh diagram of aqueous tellurium species and tellurium minerals at 250°C indicates that (Au, Ag)Te2 minerals in epithermal gold telluride mineralization would have been formed under middle to low Eh and acidic (to intermediate) pH conditions. It is possible that dilute tellurium‐containing fluid would scavenge dilute gold. Abstract : Chemical composition and mode of occurrences of (Au, Ag)Te2 minerals in epithermal gold telluride ores from some deposits in Japan are examined. Au‐Te mineralization in Japan can be divided into 4 types: native gold‐calaverite at Date and Agawa, krennerite(–native tellurium) at Osore‐zan and Mutsu, sylvanite‐native tellurium‐hessite at Teine, Kawazu, Kobetsuzawa and Kato, and polyminerallic assemblages at Suzaki and Kushikino.